Emerging psychiatric syndromes associated with antivoltage-gated potassium channel complex antibodies - Prüss, H; Lennox, B (BMJ Publishing Group, 2016)
Antibodies against the voltage-gated potassium channel (VGKC) were first recognised as having a potential pathogenic role in disorders of the central nervous system in 2001, with VGKC antibodies described in patients with limbic encephalitis, and the subsequent seminal paper describing the clinical phenotype and immunotherapy treatment responsiveness in 13 patients with VGKC antibodies and limbic encephalitis in 2004. These initial case descriptions were of a progressive neuropsychiatric syndrome with abnormalities of mood, sleep and cognition recognised alongside the neurological symptoms of seizures and autonomic instability. The clinical syndromes associated with VGKC complex (VGKCC) antibodies have broadened considerably over the last 15 years, with multiple cases of more restricted 'formes fruste' presentations associated with VGKCC antibodies being described. However, the relevance of antibodies in these cases has remained controversial. The understanding of the pathogenic nature of VGKC antibodies has further advanced since 2010 with the discovery that VGKC antibodies are not usually antibodies against the VGKC subunits themselves, but instead to proteins that are complexed with the potassium channel, in particular leucine-rich, glioma-inactivated protein 1 (LGI1) and contactin-associated protein 2 (Caspr2). Antibodies against these proteins have been associated with particular, although overlapping, clinical phenotypes, each also including neuropsychiatric features. Our aim is to critically review the association between VGKCC, LGI1 and Caspr2 antibodies with isolated psychiatric presentations-with a focus on cognitive impairment, mood disorders and psychosis. We recommend that screening for VGKCC, LGI1 and Caspr2 antibodies be considered for those with neuropsychiatric presentations.